Viabilidade agronômica de hortaliças fertilizadas com flor-de-seda (Calotropis procera (Ait.) R.Br.) - Silva, Maiele Leandro da (2012)
Three experiments (a with carrot, a with rocket and another with coriander) were conducted at the experimental farm Rafael Fernandes, from October 2010 to January 2012 with the objective of determining the amount of rooster tree incorporated into the soil and type (s) of splitting of this quantity to be used on the agroeconomic performance of carrot, as well as, of quantifying the amount (s) of rooster tree and time (s) of incorporation to be used on the agroeconomic performance of rocket and coriander. The experimental design was of randomized complete blocks with three replications, in a 4 x 3 factorial scheme for the carrot and for the rocket experiments. The treatments of the carrot experiment consisted of four amounts of rooster tree (6, 19, 32 and 45 t ha-1 on a dry basis), divided into three proportions: 30% fifteen days before sowing (DBS) + 70% thirty days after sowing (DAS), 40% fifteen days before sowing (DBS) + 60% thirty days after sowing (DAS) and 50% fifteen days before sowing (DBS) + 50% thirty days after sowing (DAS). For the experiment of the rocket, the treatments were the combinations of four quantities of rooster tree (6, 19, 32 and 45 t ha-1 on a dry basis), with three times of incorporation (10, 20 and 30 DBS). For the experiment of the coriander, the factorial scheme was 4 x 4. The treatments were the combinations of four quantities of rooster tree (7.5, 15, 22.5 and 30 t ha-1 on a dry basis), with four times of incorporation (0, 10, 20 and 30 DBS). The cultivars of carrot, rocket and coriander planted were respectively: 'Brasilia', 'Cultivada' and 'Verdão'. The characteristics evaluated in the carrot were: plant height, number of stems per plant, shoot dry mass, marketable and total yield of roots, and productivity of classified roots. For the rocket and coriander crops were: plant height, number of leaves or stems per plant, yield of green mass and dry mass of shoots. The economic indicators of gross income, net income, rate of return and profit margin were used for the economic evaluation of cultures. The highest agroeconomic performance of carrot was obtained in the amount of 45 t ha-1 of rooster tree incorporated into the soil in the splitting of 30% fifteen days before sowing (DBS) + 70% thirty days after sowing (DAS). The best agroeconomic performance of the rocket was obtained in the amount of 19 t ha-1 of rooster tree incorporated into the soil at the time of 20 days before rocket sowing. The cultivation of coriander was not agroeconomic feasible under the quantities of rooster tree incorporated into the soil and their times of incorporation studied